2018
DOI: 10.23893/1307-2080.aps.05613
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine metabolism and obesity: polyamine metabolic enzymes involved in obesity

Abstract: The natural polyamines, putrescine, spermidine and spermine are distributed widely in all cells including adipocytes. They are involved in several physiological processes involving gene expression and cell proliferation. The body pool of polyamines is maintained by endogenous biosynthesis, intestinal microorganisms and the diet. A correlation between fat metabolism and polyamine metabolism has been reported in several studies. It was shown that the inhibition of polyamine metabolism enzymes had been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…L-ornithine, in turn, is used for the synthesis of carbamoyl phosphate in the urea cycle, or alternatively as a substrate for the synthesis of polyamine via ornithine decarboxylase-1 (ODC-1). Polyamines (spermine and spermidine) are required for mammalian cell proliferation [37,53] and are involved in the adipogenesis of preadipocytes (mouse fibroblast line 3T3-L1) [54][55][56]. We observed that the expression of ODC-1 increased along with the increase in SLC14A1 expression and with increased intracellular urea concentration after urea treatment.…”
Section: Discussionmentioning
confidence: 76%
“…L-ornithine, in turn, is used for the synthesis of carbamoyl phosphate in the urea cycle, or alternatively as a substrate for the synthesis of polyamine via ornithine decarboxylase-1 (ODC-1). Polyamines (spermine and spermidine) are required for mammalian cell proliferation [37,53] and are involved in the adipogenesis of preadipocytes (mouse fibroblast line 3T3-L1) [54][55][56]. We observed that the expression of ODC-1 increased along with the increase in SLC14A1 expression and with increased intracellular urea concentration after urea treatment.…”
Section: Discussionmentioning
confidence: 76%
“…Considering the high requirement for polyamines in the first months of life, a stage of accelerated growth and development, and the potential participation of polyamines in adipogenesis ( 16 , 17 ), we studied if there was an association between the content of polyamines ingested through human milk and the infant anthropometric parameters. Most of the anthropometric indicators evaluated did not show significant correlations with the polyamine contents of human milk or polyamine intake, perhaps because all the infants in the study had an adequate nutritional status for their age, and anthropometric parameters were within normal limits (±2 SD).…”
Section: Discussionmentioning
confidence: 99%
“…SSAT catalyzes the transfer of acetyl groups from acetyl-CoA to spermidine or spermine, allowing polyamine interconversion (17,18). Thus, the dysregulation of polyamine homeostasis could have an important impact on energy metabolism and the accumulation of body fat (16,17). In fact, studies in mice report that overexpression of the SSAT enzyme caused a decrease in white adipose tissue (18,19), and the administration of spermidine or spermine reduced body weight and fat mass, in a dose-dependent manner (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prostate presents high levels of polyamines, and they increase in tumor tissues. In addition, it was shown that the inhibition of polyamine metabolism enzymes is associated with increased adipose tissue and weight gain in human and animal models ( 27 ). Alpha-difluoromethylornithine, an inhibitor of ODC, depleted the cellular polyamines and prevented triglyceride accumulation and differentiation in 3T3-L1 cells ( 28 ).…”
Section: Metabolism Dysfunction Of Periprostatic Adipose Tissue In Pr...mentioning
confidence: 99%